Biodiversity - Vandana Shiva (ed.) (Dehradun, 1992)
Conservation of Biodiversity is gaining centre stage for the environmental movement as (tropical) forests are fast disappearing, complex agriculture systems are transformed into monocultures, and about 25% of the world's flora and fauna species may be lost over the next generation. A recent study by the World Resources Institute (WRI), the World Bank, the International Union for Conservation of Nature and Natural Resources (IUCN), and the Worldwide Fund for Nature (WWF) entitled Conserving the World's Biological Diversity illustrates the flaws in many of the analyses and proposed action plans in this area of growing concern. This book by the World Rainforest Movement is a collection of essays which challenges that analysis. The contributors to this volume - all with research and campaigning experience in this field - argue that the roots of the crisis of genetic erosion lie in the industrial system of the North. This book also refutes the notion that biodiversity conservation can only be achieved if commercial interests are used to "value" genetic resources. The authors argue that Third World peasants and forest dwellers have been the guardians and beneficiaries of the world's biodiversity. They warn of emerging biotechnologies which will erode biodiversity by increasing uniformity in production, and imposing intellectual property rights to turn life forms into private property.
Keywords: Biotechnology